The adoption of Green Supply Chain Management (GSCM) by MSMEs in Tacloban City and its influence on perceived brand image among young consumers - Maula, Mitz M.; Pajarito, Patricia Joy Cabaliza; Tañala, Milenio Sam Tomol
The deterioration of ecosystems and rising global mortality rate due to toxic pollution have led to businesses facing public scrutiny and being urged to make environmental efforts, such as Green Supply Chain Management (GSCM). GSCM can be used as a competitive advantage to establish and protect brand image, especially given the growing environmental consciousness among young consumers (i.e., Generation Zs and Millennials). This study primarily investigated the level of GSCM undertaking among MSMEs in Tacloban City, Philippines, and young consumers' perceived brand image of GSCM practices, taking into account the GSCM implementation barriers and drivers. A quantitative approach was used, with MSME samples collected through stratified random sampling and consumer samples collected via purposive sampling. Data were collected through online and face-to-face Likert scale surveys. The results showed that there is a high level of GSCM implementation in Tacloban MSMEs, regardless of business size, and awareness of environmentally sustainable policies or ordinances, except for the Non-Environmentally Acceptable Packaging (NEAP) policy. There were no statistical differences between Gen Zs and Millennials' brand image perceptions. Both believe that GSCM implementation positively affects brand image. However, there is a mismatch between the GSCM practices that MSMEs are commonly adopting (i.e., Green Manufacturing) and the GSCM practices that consumers find significant in developing their perceptions of the brand (i.e., Eco-Design). The study recommends that new and existing firms integrate GSCM as it improves brand image and that the government launch education campaigns for awareness and provide procurement grants or incentives for sustainable packaging.